A Semantic Analysis of Denotative and Connotative Meaning in the Song Lyrics of “Mirrors” by Justin Timberlake - Riyanti Anjelina Sinaga; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the denotative and connotative meanings found in the song lyrics of Mirrors by Justin Timberlake. The study applied a descriptive qualitative research design because the data were analyzed in the form of words, phrases, clauses, and sentences taken from the song lyrics. The data source of this study was the official lyrics of Mirrors, released in 2013. The researcher used documentation as the technique of data collection and semantic analysis as the technique of data analysis. The findings showed that both denotative and connotative meanings were found in the lyrics. The researcher identified a total of 55 data, consisting of 22 denotative meanings and 33 connotative meanings. Denotative meanings appeared in words with literal meanings such as mirror, eyes, light, and heart. Meanwhile, connotative meanings were more dominant and appeared in symbolic expressions such as you are my mirror, my other half, and you make me complete, which represent love, identity, unity, and emotional connection. The findings indicate that connotative meaning is more dominant than denotative meaning in the song because the songwriter employs figurative and symbolic language to convey deeper emotional messages. Therefore, song lyrics can be considered an important object of semantic study because they contain rich linguistic meanings and artistic expressions.